Pengaplikasian Metode Peramalan untuk Mengoptimalkan Perencanaan Persediaan Suku Cadang (Studi Kasus: Suku Cadang Contactor di PT. Semen Padang) - Anshari, Reza Kharisma; Sukarno, Iwan (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Based on data in-out of spare parts at PT. Semen Padang, contactor type is one of the electrical spare part that have a high throughput rate compare the other sparepart type. In addition, contactors also have a high price and also needs to be stored with special treatment in the spare part warehouse. Furthermore, currently the company has not used a specific methods in determine the material requirement planning for the spare parts. Therefore in this study it is purposed to use a forecasting methods to determine the contactor requirement planning to avoid losses. Quantitaive forecasting methods was used in this study such as quadratic, cyclical, and cyclical methods. The best forecasting method is determined based on the smallest error value of the four compared methods. Contactor requirement planning is carried out by forcasting for the next 24 periods. Based on the results, it is found the best methods that has the smalles MAPE error (45%) is the Cyclic Method. The forecasting results obtained show the similarity of the trend with the historical data used, so that this forecasting method can be considered for use in material requirement planning of spare parts specially for contactor types at PT. Semen Padang.